1988
DOI: 10.1111/j.1749-7345.1988.tb01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Zinc Requirement of Oreochromis aureus and Effects of Dietary Calcium and Phytate on Zinc Bioavailability

Abstract: Two experiments were conducted to determine the dietary zinc requirement of fingerling blue tilapia (Oreochromis aureus) and the effects of dietary calcium and phytate on zinc bioavailability. Purified egg white diets containing graded levels of supplemental zinc were fed to fingerling tilapia in triplicate aquaria for 80 days. No overt signs of zinc deficiency were observed; however, scale and bone zinc concentrations of fish fed the various diets were significantly (P < 0.05) affected and increased linearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 19 publications
2
28
0
Order By: Relevance
“…We did not measure phytic acid content, but based on ingredient composition of the two feeds, we estimated diet M to contain no phytic acid and diet V to have about 0.27 % of phytic acid. It has been often observed that apparent digestibility of dietary Zn is reduced by phytic acid or calcium phytate or even by supplementation of inorganic calcium and phosphorus salts (Richardson et al 1985;Hardy and Shearer 1985;McClain and Gatlin 1988;Gatlin and Phillips 1989;Satoh et al 1989;Ramseyer et al 1999;Kousoulaki et al 2010;Antony Jesu Prabhu et al 2014a). This may explain the increased loss of dietary as well as endogenous Zn in fish fed diet V compared with diet M. Moreover, ELF of K (P = 0.11) and Mg (P = 0.15) also tended to be slightly higher in trout fed diet V, as reported in piglets when fed diets containing phytic acid (Woyengo et al 2009).…”
Section: Starvation Loss (Sl) and Endogenous Loss Of Fed Fish (Elf)mentioning
confidence: 99%
“…We did not measure phytic acid content, but based on ingredient composition of the two feeds, we estimated diet M to contain no phytic acid and diet V to have about 0.27 % of phytic acid. It has been often observed that apparent digestibility of dietary Zn is reduced by phytic acid or calcium phytate or even by supplementation of inorganic calcium and phosphorus salts (Richardson et al 1985;Hardy and Shearer 1985;McClain and Gatlin 1988;Gatlin and Phillips 1989;Satoh et al 1989;Ramseyer et al 1999;Kousoulaki et al 2010;Antony Jesu Prabhu et al 2014a). This may explain the increased loss of dietary as well as endogenous Zn in fish fed diet V compared with diet M. Moreover, ELF of K (P = 0.11) and Mg (P = 0.15) also tended to be slightly higher in trout fed diet V, as reported in piglets when fed diets containing phytic acid (Woyengo et al 2009).…”
Section: Starvation Loss (Sl) and Endogenous Loss Of Fed Fish (Elf)mentioning
confidence: 99%
“…The 7% tristearin and menhaden oil diets were used again as EFA-deficient and control diets, respectively. Procedures for diet preparation were as previously described (McClain and Gatlin 1988). In addition, all diets were supplemented with 125 mg ethoxyquin/kg.…”
Section: Experimental Dietsmentioning
confidence: 99%
“…The dietary Zn requirement of tilapia also had been studied (Do Carmo et al, 2004, 2005Eid and Ghonim, 1994;Lin et al, 2008;McClain and Gatlin, 1988). The tilapia in these previous studies were of small size (average initial body mass less than 5 g), whereas the Zn requirement of large tilapia has received little attention.…”
Section: Introductionmentioning
confidence: 99%